Implementasi PSAK Syariah terhadap Kualitas Pelaporan Keuangan Lembaga Keuangan Islam - Nashrul Muminin (Jurnal Akuntansi dan Bisnis Syariah, 2026)
This study aims to analyze the implementation of Sharia PSAK on the quality of financial reporting at Islamic financial institutions, focusing on a case study at the Yogyakarta Branch Office of Bank Syariah Indonesia (BSI). The implementation of Sharia PSAK is a crucial instrument in ensuring that financial reports are prepared in accordance with Sharia principles, are transparent, and accountable, and can increase stakeholder trust in Islamic financial institutions. The primary objective of this study is to determine the extent to which the implementation of Sharia PSAK impacts the quality of financial reporting, including aspects of relevance, reliability, timeliness, and comparability.The research method used is a descriptive qualitative approach with a case study. Data were obtained through observation, interviews with accounting and finance staff, and documentation of financial reports for the 2023–2026 period. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. Furthermore, this study used a percentage measurement of compliance with Sharia PSAK implementation to more measurably assess the quality of financial reporting.The results indicate that the implementation of Sharia PSAK at the Yogyakarta Branch Office of BSI has been running quite optimally, with a compliance rate of 85%. The quality of financial report relevance reached 83%, reliability reached 87%, reporting timeliness reached 78%, and comparability reached 80%. Overall, the implementation of PSAK Sharia has been proven to have a positive impact on improving the quality of financial reporting at Islamic financial institutions, although there are still challenges in terms of system digitalization and human resource training that need to be improved.